Pros and Cons of Separation between Maqāṣid and Uṣūl al-Fiqh (A Study of The Periodization of Maqāṣid History and Responses to Its Independence) - Tholkhatul Khoir (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
Interests related to human needs always invite the possibility of the birth of new knowledge. However, if it differs from previous beliefs and ideologies, the findings from the embryonic new knowledge research should be addressed. Currently, the maqāṣid has become the most popular research theme in the field of Islamic legal theory and eclipsed uṣūl al-fiqh was facing such challenges. This article explores the evidence for the pros and cons of the separation between maqāṣid and uṣūl al-fiqh, explains the causes, and predicts the implications. Data was obtained from secondary sources in the form of maqāṣid and uṣūl al-fiqh works, both in the form of books, book reviews, journal articles, and dissertations, obtained from the web and libraries, and then analyzed using content analysis. This paper finds that there are indeed pros and cons of separating maqāṣid and uṣūl al-fiqh. The evidence is: first, there are differences in periodizing the development of maqāṣid; and second, there are differences in responses to efforts to make maqāṣid an independent knowledge. The pros and cons are triggered by differences of opinion regarding the theory of ratiocination, the method of istiqrā', and accusations of utilitarianism. These pros and cons can have implications: positive, because in turn, the Islamic law reform project can be handled more comprehensively, or negative, if the scholars get caught up and struggle with the debate until they forget to respond to real contemporary issues.